INVASIVE PNEUMOCOCCAL DISEASES IN CHILDREN AGED 1-59 MONTHS IN SICILY, ITALY: IMPORTANCE OF ACTIVE FAMILY PAEDIATRICIAN SURVEILLANCE AND VACCINATION COVERAGE. - Emanuele Amodio (Euromediterranean Biomedical Journal, 2014)
Purpose: Aim of this study was to analyze pediatric invasive pneumococcal disease rates several years after the implementation of infant pneumococcal vaccination. Methods: The study was carried out in Sicily and involved about 30,000 children, aged 1- 59 months, actively monitored by 100 family pediatricians during 2010 and 2011. All children who met the inclusion criteria were considered eligible, recorded using a standardized case report form and investigated for the presence of S. pneumoniae in specimens from sterile sites. Results: None of the 40 eligible children was confirmed as a case of invasive pneumococcal disease. The incidence rate of invasive pneumococcal disease cases was 0.0/100,000 in both years. Regional childhood pneumococcal vaccination coverage rates were 90.7% in 2010 and 92.0% in 2011. Conclusions: Our results show that during the study period invasive pneumococcal disease cases were rare in Sicilian children, suggesting a very effective control of the disease in a region with very high vaccination coverage against S. pneumoniae